The Image of Women in Novel "Istri Kedua" by Asma Nadia and Isa Alamsyah (Feminism Studies) - Rose Junieles; Sri Lestari (Aksis : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Novel "Istri Kedua" tells the story of polygamy experienced by several women. This story is a true story written by Asma Nadia and Isa Alamsyah. The image of women in this matter was taken because, some people still think that women are weak creatures and are easily deceived, so the depiction of a woman will prove that women have a better image than other people think. Novel "Istri Kedua" is analyzed with feminism theory, feminism theory is taken because feminism is a study that opposes patriarchal culture. The method used in this research is qualitative description with data in the form of paragraphs, sentences, and words related to the image of women. The results found are, the image of women is divided into two, namely the self-image of women and the social image of women. The self-image of women based on the self depicted by women both physically and psychologically, while the social image of women is reflected in the behavior of women both in the family and in society.